The Role of Social Media In Shaping Brand Image: A Case Study of the Online Fashion Industry - Simangunsong, Martua Erikson; Tiara, Cindy (Jurnal Manajemen, Informatika, Rekayasa Perangkat Lunak dan Teknologi Komunikasi, 2023)
This research aims to investigate the role of social media in shaping brand image in the online fashion industry and analyse the application of brand differentiation methods as a strategy to overcome challenges in a dynamic social media environment. Using a qualitative approach, data was collected through case studies on several online fashion brands active on social media. The results show that companies can leverage personalisation of consumer experience, augmented reality technology, and collaboration with influencers to differentiate their brands from competitors and strengthen brand image in an increasingly competitive market. However, this study has limitations in coverage which focused on the online fashion industry and brand differentiation methods, so it is recommended for future research to expand the coverage and deepen the understanding of other factors that influence brand image in the context of social media..